3D macro- and microfabric analyses of Neoproterozoic diamictites from the Valjean Hills, California (United States) - Kettler, C.; Phillips, E.; Pichler, K.; Smrzka, D.; Vandyk, T. M.; Le Heron, D. P. (Frontiers in Earth Science, 2023)
Neoproterozoic rocks from the Kingston Peak Formation (KPF) in the Valjean Hills (USA) expose a succession of diamictites associated with major glacial events taking place during the Cryogenian, approximately 700 million years ago. Within any glacial period, diamictites are widespread and in addition, their mechanics of deposition are highly variable. Some are massive in appearance at outcrop or in hand specimens, and apparently lacking any information that allows their mode of emplacement to be elucidated. Yet the correct interpretation for deep time successions in this area is especially important, since it is debated whether the diamictites are either associated to a tectonically driven origin, associated with rifting at the south western Laurentian margin alongside slope controlled gravitational mass movement, or predominantly deposited as (sub)glacial diamictites. In this contribution we determine the direction of deposition of diamictites based on their internal microfabric and associated microstructures. We base our method on the technique of Phillips et al. (2011) for Quaternary sediments, by mapping the apparent longest axes of skeleton grains (ranging from fine-grained sand to fine-grained pebbles) in oriented thin sections and reconstructing their microfabric in a 3D space coupled with macro fabric data for each diamictite. In this way we could identify a bimodal signal in the orientation of the longest axes for each sample. Evidence for shearing and soft sediment deformation supports either subaqueous or subglacial deposition with deformation induced by basal sliding with a paleo flow directed towards the southeast.